(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article in pieces of integration simpler ways given also two _ _ and in it more than in pieces to integration circle functions generalized in pieces integration method faster to the solution have to be seeing let’s go out, one from one we distinguish and given examples one by one analysis we do